2021
DOI: 10.1109/jphot.2021.3106584
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Monolithic Passive-Matrix GaN-Based MicroLED Arrays With Pixel Sizes From 5 to 50 µm

Abstract: MicroLED arrays with the capability of switching each pixel separately with high frequency can serve as structured micro-illumination light engines for applications in sensing, optogenetics, microscopy and many others. We describe a scalable chip process chain for the fabrication of passive-matrix microLED arrays, which were integrated with PCB-based driving electronics. The arrays were produced by deep-etching of conventional planar LED structures on sapphire, followed by filling and planarization steps. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For example, Guo et al [25], investigating interdigitated mesas of LEDs, experimentally found that a narrower mesa that has a relatively longer sidewall dimension resulted in a higher η e . For µLEDs, an increasing EQE with shrinking size could be attributed to the increasing total η e via a higher contribution from sidewall emission [26][27][28]. Considering the impact of sidewall emission on η e , it could be interpreted that a larger peak EQE for a longer periphery (regardless of the device area shown in figure 2) is associated with increasing η e .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Guo et al [25], investigating interdigitated mesas of LEDs, experimentally found that a narrower mesa that has a relatively longer sidewall dimension resulted in a higher η e . For µLEDs, an increasing EQE with shrinking size could be attributed to the increasing total η e via a higher contribution from sidewall emission [26][27][28]. Considering the impact of sidewall emission on η e , it could be interpreted that a larger peak EQE for a longer periphery (regardless of the device area shown in figure 2) is associated with increasing η e .…”
Section: Resultsmentioning
confidence: 99%
“…Second, we speculate that the change in η e is related not only to the device area but also to the length of the light propagation and the emission width of the device. It has been demonstrated that η e can increase with shrinking device size due mostly to the reduced light propagation length resulting in an increased EQE [26][27][28]. Assuming the light propagation lengths of 160 × 40 µm 2 and 160 × 10 µm 2 devices to be 40 µm and 10 µm, respectively, it is understood that a shorter light propagation length yields a larger η e , resulting in the ratio of 160 × 10 µm 2 to 160 × 40 µm 2 devices being greater than 1.0 over the whole current regime.…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of the matrix-addressed LED arrays ( Figure 1 c) is described in detail in a previous publication [ 51 ]. It consists of 32 × 32 squared LEDs of 50 µm edge length edge length with 100 µm pitch ( Figure 1 c).…”
Section: Methodsmentioning
confidence: 99%
“…The driver can operate up to 10 V, thus allowing the LED to provide high optical power (~30 µW at 6 V [ 51 ]). The capability of these drivers to generate driving voltages up to 10 V also enables the circuit to be used to drive nanoLEDs [ 54 ], which usually work at a higher voltage bias [ 55 ] because of the high resistance associated with the interconnection of the LED with the CMOS [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, in the work of Bornemann et al, they used etched n-GaN as the cathode line. However, using semiconductor as the electrode line increased the resistance [14] .…”
Section: Introductionmentioning
confidence: 99%